A Boundary Value Problem for the Degenerated Elliptic Equation with Singular Coefficient and Spectral Parameter (Journal of Partial Differential Equations, 2018)
In this paper, the Dirichlet problem in the vertical half-band for the degeneratedelliptic equation with singular coefficient and spectral parameter is investigated.Using the Hankel transformation and the method of separation of variables, the solutionof the Dirichlet problem is presented in the explicit form.